The Macedonian question and the Macedonians - Heraclides, Alexis, author.
1 online resource
Keywords: This book is a comprehensive and dispassionate analysis of the intriguing Macedonian Question from 1878 until 1949 and of the Macedonians (and of their neighbours) from the 1890s until today, with the two themes intertwining. The Macedonian Question was an offshoot of the wider Eastern Question - i.e., the fate of the European remnants of the Ottoman Empire once it dissolved. The initial protagonists of the Macedonian Question were Greece, Bulgaria and Serbia, and a Slav-speaking population inhabiting geographical Macedonia in search of its destiny, the largest segment of which ended up creating a new nation, comprising the Macedonians, something unacceptable to its three neighbours. Alexis Heraclides analyses the shifting sands of the Macedonian Question and of the gradual rise of Macedonian nationhood, with special emphasis on the Greek, Bulgarian and Serbian claims to Macedonia (1870s-1919); the birth and vicissitudes of the most famous Macedonian revolutionary organization, the VM(O)RO, and of other organizations (1893-1940); the appearance and gradual establishment of the Macedonian nation from the 1890s until 1945; Titos's crucial role in Macedonian nationhood-cum-federal status; the Greek-Macedonian name dispute (1991-2018), including the skeletons in the cupboard' - the deep-seated reasons rendering the clash intractable for decades; the final Greek-Macedonian settlement (the 2018 Prespa Agreement); the Bulgarian-Macedonian dispute (1950-today) and its ephemeral settlement in 2017; the issue of the Macedonian language; and the Macedonian national historical narrative. The author also addresses questions around who the ancient Macedonians were and the fascination with Alexander the Great. This monograph will be an essential resource for scholars working on Macedonian history, Balkan politics and conflict resolution.